Male Perception of Female Participation and VAW on the Virtual Learning App – “Hallo” - Aziza Hena (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2022)
This study explored men's perception of women's participation and VAW (Violence against women) on an online learning platform called